PEMBERDAYAAN ANAK JALANAN MELALUI PENDEKATAN PEKERJAAN SOSIAL - Nuraini Widad (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2019)
Children who are displaced on the street without family care are often referred to as street children. Those born of two aspects, the first because of a family problem or a broken home that they finally plunge into the harsh world, second because of the support of free association and mischoosing a friend. This becomes one of the problems of vulnerability in the future of the child, in the capital the number of street children increasingly increasing the day. A wide variety of street children's lives, ranging from sleeping under bridges, rail tracks, to living on the market. Not only in the capital, even now the street children are rampant in various regions. This problem should be addressed immediately because the future of the nation there is the hand of youth, if the princes are troubled how about the people. Social workers are one solution to tackle a child's future vulnerability problem. With various activities and motivation encouragement that social workers do can change the life of street children.